English for Science Students: Teacher's Book: учебное пособие - Обдалова О. А.; Айлазян Е. П. Елена Прокопьевна; Гураль С. К.; Шабунина Т. А.; Экклес Т. А. (Томск, Изд-во Томского ун-та, 2010)
В фонде НТБ ТПУ отсутствует